2018
DOI: 10.21037/atm.2017.10.17
|View full text |Cite
|
Sign up to set email alerts
|

A review of racial disparities in transcatheter aortic valve replacement (TAVR): accessibility, referrals and implantation

Abstract: Racial disparities in transcatheter aortic valve replacement (TAVR) implantation results from several factors, including socioeconomic disparities, inherent biases in healthcare provision, fewer referrals to specialists and language barriers in some minority populations. In this review article, we discuss the current data on the racial disparities in TAVR, explore the prevalence of aortic stenosis in different demographics in the United States and we proffer practical solutions to these problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Minha et al found that black patients are more likely to refuse AVR as compared to whites . Lower socioeconomic status and lack of health insurance limit the number of PPM implantations among black population . It is worth noting however that due to limitations of our database, it is unknown whether black patients who developed CHB after TAVR were more likely to recover as compared to their white counterparts.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Minha et al found that black patients are more likely to refuse AVR as compared to whites . Lower socioeconomic status and lack of health insurance limit the number of PPM implantations among black population . It is worth noting however that due to limitations of our database, it is unknown whether black patients who developed CHB after TAVR were more likely to recover as compared to their white counterparts.…”
Section: Discussionmentioning
confidence: 88%
“…32 Lower socioeconomic status and lack of health insurance limit the number of PPM implantations among black population. 29 It is worth noting however that due to limitations of our database, it is unknown whether black patients who developed CHB after TAVR were more likely to recover as compared to their white counterparts. Further studies are needed to determine the driv- In addition to increased risk of mortality, the development of CHB had significant impact on hospital LOS and hospitalization cost.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Transcatheter aortic valve replacement (TAVR) has recently become the mainstay of treatment for many patients with severe aortic stenosis (AS) that otherwise are considered at an inordinate risk to undergo surgical replacement [1]. Nonetheless, following the historical trend of other novel advances in the cardiovascular field, TAVR clinical studies have been mainly focused on Caucasian populations with limited representation of minority groups [2,3]. Previous studies have shown that along with African Americans (AA), Hispanics are a target of significant cardiovascular disparities and burdened with a higher prevalence of cardiovascular disease than their Caucasian counterparts [4].…”
Section: Introductionmentioning
confidence: 99%